PET and SPECT imaging for the acceleration of anti-cancer drug development - Hillyar, C; Knight, J; Vallis, K; Cornelissen, B (Ingenta, 2015)
Lead-compound optimization is an iterative process in the cancer drug development pipeline, in which small molecule inhibitors or biological compounds that are selected for their ability to bind specific targets are synthesised, tested and optimised. This process can be accelerated significantly using molecular imaging with nuclear medicine techniques, which aim to monitor the biodistribution and pharmacokinetics of radiolabelled versions of compounds. Positron emission tomography (PET) and single-photon emission computed tomography (SPECT) can be used to quantify fourdimensional (temporal and spatial) clinically relevant information, to demonstrate tumor uptake of, and monitor the response to treatment with lead-compounds. This review discusses the pre-clinical and clinical value of the information provided by nuclear medicine imaging compared to the histological analysis of biopsied tissue samples. Also, the role of nuclear medicine imaging is discussed with regard to the assessment of the treatment response, radiotracer biodistribution, tumor accumulation, toxicity, and pharmacokinetic parameters, with mention of microdosing studies, pre-targeting strategies, and pharmacokinetic modelling.